2012
DOI: 10.1002/bmc.2731
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and sensitive liquid chromatography–tandem mass spectrometric assay for moexipril, an angiotensin‐converting enzyme inhibitor in human plasma

Abstract: A simple, rapid and sensitive liquid chromatography/tandem mass spectrometry method was developed and validated for the quantification of angiotensin-converting enzyme inhibitor, moexipril, in human plasma. Benazepril was used as an internal standard (IS). Analyte and IS were extracted from the human plasma by liquid-liquid extraction technique using ethyl acetate. The reconstituted samples were chromatographed on a C₁₈ column by using a mixture of methanol and 0.1% formic acid buffer (85:15, v/v) as the mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Also, in 2012, Karra et al developed a method for determination of MOX by LC-Tandem mass spectrometry. But MOXT, which is the active metabolite was not determined [11].…”
Section: Moexipril (3s)-2-[(2s)-2-[[(1s)-1-(ethoxycarbonyl)-3-phenylpmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in 2012, Karra et al developed a method for determination of MOX by LC-Tandem mass spectrometry. But MOXT, which is the active metabolite was not determined [11].…”
Section: Moexipril (3s)-2-[(2s)-2-[[(1s)-1-(ethoxycarbonyl)-3-phenylpmentioning
confidence: 99%
“…It is reported that MOX was identified by HPLC [4][5][6], spectrophotometry [7,8], gas chromatography mass spectrometry [9], and liquid chromatography tandem mass spectrometry [10,11]. In 2006, Koti, J. et al developed a LC-MASS spectrometry method just to monitor the metabolism of MOX to MOXT [10].…”
Section: Moexipril (3s)-2-[(2s)-2-[[(1s)-1-(ethoxycarbonyl)-3-phenylpmentioning
confidence: 99%
“…Moexiprilat, in human plasma [8]. Karraa et al developed a rapid and sensitive liquid chromatography-tandem mass spectrometric assay for MOX in human plasma [9]. As there are no reports available on the degradation behavior, identification and characterization of Degadaation Products (DPs) of MOX formed under various stress conditions, we have carried out a detailed study on stability indicating LC-MS/MS method for MOX.…”
Section: Biochemistry and Analytical Biochemistrymentioning
confidence: 99%
“…Finally we achieved a good resolution of peaks with acceptable shape with mobile phase consisting of 20 mM ammonium acetate buffer (A), pH adjusted to 6.0 using dilute formic acid and methanol (B) in a gradient elution program. The gradient program for mobile phase solvents was set as follows, (T min / %solution of B): 0-0 /30, 0-5 /65, [5][6][7][8][9][10][11][12][13][14][15] /65, 15-20 /30. The mobile phase flow rate of 1.0 ml/min, column temperature of 25°C and wavelength of 273 nm were found to be suitable for the chromatographic separation of MOX and its DPs.…”
Section: Optimization Of Lc-ms Conditionsmentioning
confidence: 99%
“…Karra et al () have reported LC–MS method for quantitative determination of moexipril in human plasma. An HPLC method for the quantitative determination of moexipril in pharmaceutical dosage forms was developed and applied to the assay of moexipril in tablet and bulk form (Elshanawane, Mostafa, & Elgawish, ).…”
Section: Introductionmentioning
confidence: 99%